2002
DOI: 10.1007/s00894-002-0074-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure-toxicity relationships study of a series of organophosphorus insecticides

Abstract: Structure-toxicity relationships were studied for a set of 47 insecticides by means of multiple linear regression (MLR) and artificial neural network (ANN). A model with three descriptors, including shape surface [S(R2)], hydrogen-bonding acceptors [HBA(R2)] and molar refraction [MR(R1)], showed good statistics both in the regression (r = 0.875, s = 0.417 and q2 = 0.675) and artificial neural network model with a configuration of [3-5-1] (r = 0.966, s = 0.200 and q2 = 0.647). The statistics for the prediction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…These results are expectable since several previous reports demonstrated that when ANNs were trained with variables selected by linear search routines, the networks largely overcame linear models by increasing data fitting but the predictors did not exhibit a remarkable improvement in predictive power [15,17,20,46]. In such cases ANNs were able to learn the data very well but they were not stable enough predicting the activity of newer compounds presented to the networks.…”
Section: Ga Based Multilinear Regressions Analysissupporting
confidence: 51%
“…These results are expectable since several previous reports demonstrated that when ANNs were trained with variables selected by linear search routines, the networks largely overcame linear models by increasing data fitting but the predictors did not exhibit a remarkable improvement in predictive power [15,17,20,46]. In such cases ANNs were able to learn the data very well but they were not stable enough predicting the activity of newer compounds presented to the networks.…”
Section: Ga Based Multilinear Regressions Analysissupporting
confidence: 51%
“…Similar substituent-based schemes have been successfully used for input encoding in NN-based methods: QSPR applications predicting the toxicity of organophosphorus insecticides [71] and in QSAR applications on a set of benzodiazepines used in treatment of anxiety and emotional disorders [72], or on analogues of the hept inhibitors of HIV-1 reverse transcriptase [73].…”
Section: Discussionmentioning
confidence: 99%
“…Target data files include targets (normalized measured shear stress values respectively of input data sets) for training, validation and testing data sets. The work in this paper included a function approximation or prediction problem that required the final error to be reduced to a very small value [7,8]. The training stopped after 1000 epochs because the validation error increased.…”
Section: Fig 4 Abbreviated View Of Lm20tp Model In Matlab Windowmentioning
confidence: 99%